Simulation and analysis performance of turbo codes and convolutional codes using BPSK modulation technique in WCDMA environment / Siti Shuhada Othman - Othman, Siti Shuhada (2009)
This project illustrates the analysis performance of BPSK modulation between convolutional codes and turbo codes in WCDMA environment by using simulation technique. In this project, the WCDMA system is considered and the performance of both codes is investigated. Turbo and convolutional codes are used to encode and decode the digital signal before modulation and after modulation process. The main objective is to compare the performance between both codes for digital communication system in different sizes; 256, 512 and 1024 bits. The analysis performances are compared and evaluated by means of bit error rates of BPSK modulation between these codes in AWGN channel for WCDMA applications. This project is simulated by using MATLAB version 7.6.